Synergistic activity of linifanib and irinotecan increases the survival of mice bearing orthotopically implanted human anaplastic thyroid cancer - Banchi, Marta (Am J Cancer Res, 2020)
Anaplastic thyroid cancer (ATC) is the most aggressive form of thyroid cancer, and novel combined therapies are urgently needed to prolong patient survival. No data are currently available on the preclinical activity of the combination of linifanib, a CSF-1R inhibitor, and irinotecan in ATC. The aim of the study was to evaluate the in vitro and in vivo activity of linifanib plus irinotecan. Proliferation and apoptosis assays were performed on 8305C and 8505C human ATC cell lines exposed to SN-38, the active metabolite of irinotecan, linifanib alone, and their concomitant combination. Synergism was evaluated by the combination index method. Quantification of pospho-CSF-1R levels was performed by ELISA. In vivo ATC orthotopic xenografts were treated with the single drugs, or their combination, to evaluate their impact on survival. Histology and immunohistochemistry were performed on ATC tissue samples. Both SN-38 and linifanib inhibited in vitro the proliferation of 8305C and 8505C cells in a concentration-dependent manner, whereas their concomitant treatment revealed a strong synergism in the ATC cells. A significant pro-apoptotic activity was found in both ATC cell lines treated with linifanib alone and in combination with SN-38. Moreover, linifanib significantly decreased the levels of phospho-CSF-1R after 24 h and 72 h in both 8505C and 8305C cells, and this was also observed with the concomitant administration of SN-38. In vivo, the combination of linifanib and irinotecan produced a greater survival result than either monotherapy, and resulted in a significant higher median survival. In some of the mice the combination produced a complete response with a macroscopic disappearance of the disease, as confirmed by histology. In conclusion, the synergistic ATC antitumor activity of linifanib/irinotecan combination significantly increased the survival of ATC affected mice and induced some complete responses, suggesting a potential role of this schedule in ATC patient’s treatment.